2017
DOI: 10.4081/reumatismo.2017.978
|View full text |Cite
|
Sign up to set email alerts
|

Work-related carpal tunnel syndrome treatment: a cross-sectional study among 106 patients

Abstract: SUMMARYThe objective is to assess the influence of sociodemographic, professional and clinical variables on the choice of treatment of work-related carpal tunnel syndrome (CTS). An exhaustive and trans-sectional study was conducted over a period of eight years, from 1st January 2006 to 31 December 2013 in the Department of Occupational Medicine at University Hospital of Mahdia, Tunisia. The study population was represented by patients with work-related carpal tunnel syndrome. Data collection was based on a que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Checkout operators in supermarkets, cashiers, and assembly line workers are also at risk of developing CTS ( 15 ). Furthermore, numerous workers in the clothing industry were affected by this ailment, establishing a connection between CTS as a professional disease and this complex industry ( 19 ). Interestingly, individuals engaged in electrical (TV) assembly have an increased risk of developing CTS due to the complex manipulation of extremely small components and wiring, exerting constant and continuous pressure on the median nerve ( 20 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Checkout operators in supermarkets, cashiers, and assembly line workers are also at risk of developing CTS ( 15 ). Furthermore, numerous workers in the clothing industry were affected by this ailment, establishing a connection between CTS as a professional disease and this complex industry ( 19 ). Interestingly, individuals engaged in electrical (TV) assembly have an increased risk of developing CTS due to the complex manipulation of extremely small components and wiring, exerting constant and continuous pressure on the median nerve ( 20 ).…”
Section: Resultsmentioning
confidence: 99%
“…It has been observed that chronic compression can result in demyelination, axonal loss, and hypoxia, contributing to both motor and sensory deficits specific to CTS ( 46 ). Importantly, inflammation, oxidative stress, and ischemia emerge as prominent pathophysiological features of this chronic condition ( 19 ). Previous studies have linked nerve edema and fibrosis to chronic inflammation, which exacerbates compression within the carpal tunnel ( 18 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations